Thermodynamics and Fluctuations far from Equilibrium - Ross, John.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book deals with the formulation of the thermodynamics of chemical and other systems far from equilibrium, including connections to fluctuations. It contains applications to non-equilibrium stationary states and approaches to such states, systems with multiple stationary states, stability and equi-stability conditions, reaction diffusion systems, transport properties, and electrochemical systems. The theoretical treatment is complemented by experimental results to substantiate the formulation. Dissipation and efficiency are analyzed in autonomous and externally forced reactions, including several biochemical systems.
Thermodynamics and Fluctuations Far from Equilibrium -- to Part I -- Thermodynamics Far from Equilibrium: Linear and Nonlinear One-Variable Systems -- Thermodynamic State Function for Single and Multivariable Systems -- Continuation of Deterministic Approach for Multivariable Systems -- Thermodynamic and Stochastic Theory of Reaction–Diffusion Systems -- Stability and Relative Stability of Multiple Stationary States Related to Fluctuations -- Experiments on Relative Stability in Kinetic Systems with Multiple Stationary States -- Thermodynamic and Stochastic Theory of Transport Processes -- Thermodynamic and Stochastic Theory for Non-Ideal Systems -- Electrochemical Experiments in Systems Far from Equilibrium -- Theory of Determination of Thermodynamic and Stochastic Potentials from Macroscopic Measurements -- Dissipation and Efficiency in Autonomous and Externally Forced Reactions, Including Several Biochemical Systems -- Dissipation in Irreversible Processes -- Efficiency of Irreversible Processes -- Finite-Time Thermodynamics -- Reduction of Dissipation in Heat Engines by Periodic Changes of External Constraints -- Dissipation and Efficiency in Biochemical Reactions -- Three Applications of Chapter 16 -- Stochastic Theory and Fluctuations in Systems Far from Equilibrium, Including Disordered Systems -- Fluctuation–Dissipation Relations -- Fluctuations in Limit Cycle Oscillators -- Disordered Kinetic Systems.
Keywords: Amorphous substances; Complex fluids; Physical chemistry; Soft and Granular Matter, Complex Fluids and Microfluidics; Physical Chemistry